2009
DOI: 10.1504/ijvd.2009.024244
|View full text |Cite
|
Sign up to set email alerts
|

Exhaust emissions estimation during transient turbocharged diesel engine operation using a two-zone combustion model

Abstract: A comprehensive, two-zone, transient, diesel combustion model is used to study the performance and exhaust emissions of a turbocharged diesel engine during load transients. Analytical modelling of fuel spray and in-cylinder processes is included, while detailed equations concerning all engine subsystems describe the phenomena, which diversify transient operation from the steady-state. Demonstrative diagrams are provided for the time histories of nitric oxide (NO) and soot emissions during transient operation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…To predict these emissions from diesel engines, Rakopoulos et al used a comprehensive, 2-zone, transient, diesel combustion model and found that both the NO and the soot emissions were higher in the exhaust values during transient than in steady-state conditions [1]. Pawar and Kulkarni studied a numerical method to predict the NO x emissions by considering the parameter equivalence ratio and the study showed that when the equivalence ratio increases, the NO x increases [2].…”
Section: Introductionmentioning
confidence: 99%
“…To predict these emissions from diesel engines, Rakopoulos et al used a comprehensive, 2-zone, transient, diesel combustion model and found that both the NO and the soot emissions were higher in the exhaust values during transient than in steady-state conditions [1]. Pawar and Kulkarni studied a numerical method to predict the NO x emissions by considering the parameter equivalence ratio and the study showed that when the equivalence ratio increases, the NO x increases [2].…”
Section: Introductionmentioning
confidence: 99%
“…The principal source of NO is oxidation of atmospheric nitrogen. As the consideration of chemical equilibrium cannot correctly predict NO concentration, a generally accepted kinetics formation scheme described by an extended Zeldovich model [36] is used in this study. The reactions of the extended Zeldovich model are shown in Reactions (15)- 17:…”
Section: No X Formation Kinetic Modelmentioning
confidence: 99%
“…However, these engines require very complex after-treatment devices to meet stringent emission targets for NOx and soot, on transient legislative cycles as well as on different transient cycles representing field operations. There are differences in NOx and soot emissions between operation under transient condition with speed or load increase and their corresponding steady state speed-load points [1]. Hence, to meet transient cycle emissions with low cost after-treatment devices as well as to achieve lower emissions in real operations, engines are required to be specifically optimised for transient emissions.…”
Section: Introductionmentioning
confidence: 99%